Dissecting the Roles of LncRNAs in the Development of Periventricular White Matter Damage - Wang, Xinyu; Liu, Heng; Liao, Xiaoli; Qiao, Lixing; Zhu, Lihua; Wu, Shun; Zhou, Yan; Zhang, Yi; Li, Bangbang; Lin, Lili; Ma, Jingjing; Gu, Qianying; et al. (Frontiers in Genetics, 2021)
Long non-coding RNA (LncRNA) has high expression in the brain. Animal studies have shown that lncRNA plays an important role in brain functions and mediates the development of many neurological diseases. However, data on the expression of lncRNAs and the clinical significance in prematurely born infants with diseases such as periventricular white matter damage (PWMD) remains scant. Here, we compared the expression of the lncRNAs in whole blood samples obtained from prematurely born infants with PWMD, with samples from prematurely born infants without the PWMD. Our data demonstrated differential expression of the lncRNAs between the two groups. Further, we showed that the lncRNAs play important roles in the development of PWMD. Our findings give insights into the functions of the lncRNAs in PWMD and provide evidence for the improvement of diagnostic and treatment strategies in infants with PWMD.